Study of the Effect of Hydro-Alcoholic Extract of Lactuca sativa on Arterial Blood Pressure and Heart Rate in Rats - Razieh . Dehbooreh; Zahra Heshmatian; Leila Ashrafi Babaganjeh; Mohammad Hasan Khadem Ansary; Leily Ashrafi; Peivand Bahramy Azar; Mohammad Rahim Abdollahy; Behnam Heshmatian (پزشکی بالینی ابن سینا, 2013)
Introduction & Objective: Cardiovascular diseases are main causes of mortality and morbidity in the current world. Hypertension is one of the most important risk factors for the cardiovascular diseases. Herbal medicine is much regarded because of their natural source and less side effects. This study was done to evaluate the effects of hydro- alcoholic extract of Luctuca-Sativa (LS) on blood pressure in rats.